Collaboration as graphs: Formatting Collaborative Design generative sessions from Social Network Analysis - Parolin, Guilherme; Koltermann da Silva, Tânia Luisa (AWARI, 2023)
Social Network Analysis (SNA) is demonstrably efficient as a method for studying several phenomena. However, its application as a basis for analysing in-person collaborative design sessions is still relatively scarce. Thus, this paper studies, in an exploratory manner, the applicability of SNA as an auxiliary framework for building co-creative design sessions. For that purpose, this research facilitated a generative session in a real context of a product design project. The interactions which took place during the session were analysed through SNA via the establishment, in the shape of graphs, of the perceived interactions by participants. The development process of facilitating materials for the generative session, such as its sensibilization kit, and other support media, is exemplified and possibilities of analysis for the sociograms developed are proposed. It concludes that SNA has the potential as a tool to provide analysis and subsequent systematic intervention in Collaborative Design sessions.